2017
DOI: 10.7150/thno.17322
|View full text |Cite
|
Sign up to set email alerts
|

Obatoclax and LY3009120 Efficiently Overcome Vemurafenib Resistance in Differentiated Thyroid Cancer

Abstract: Although the prognosis of differentiated thyroid cancer (DTC) is relatively good, 30-40% of patients with distant metastases develop resistance to radioactive iodine therapy due to tumor dedifferentiation. For DTC patients harboring BRAFV600E mutation, Vemurafenib, a BRAF kinase inhibitor, has dramatically changed the therapeutic landscape, but side effects and drug resistance often lead to termination of the single agent treatment. In the present study, we showed that either LY3009120 or Obatoclax (GX15-070) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Along this line, in this report we, for the first time, identified survivin as a novel molecule targeted by Obatoclax to induce apoptosis. Notably, given both survivin and antiapoptotic BCL-2 proteins represent two integral branches of pro-survival mechanisms that promote therapeutic resistance of cancer cells, our discovery that Obatoclax downregulates survivin aside from inhibiting anti-apoptotic BCL-2 proteins is clinically attractive regarding the use of Obatoclax to facilitate drug sensitization in cancer cells with inherent or acquired resistance to cancer therapeutics [16,26,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, in this report we, for the first time, identified survivin as a novel molecule targeted by Obatoclax to induce apoptosis. Notably, given both survivin and antiapoptotic BCL-2 proteins represent two integral branches of pro-survival mechanisms that promote therapeutic resistance of cancer cells, our discovery that Obatoclax downregulates survivin aside from inhibiting anti-apoptotic BCL-2 proteins is clinically attractive regarding the use of Obatoclax to facilitate drug sensitization in cancer cells with inherent or acquired resistance to cancer therapeutics [16,26,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Although the detailed role of autophagy in the pathogenesis of thyroid cancer is not yet elucidated (Netea-Maier et al 2015), recent studies shed light on the underlying mechanisms of autophagy in regulating the development and dedifferentiation of thyroid cancers (Plantinga et al 2016, Tesselaar et al 2017a, Tesselaar et al 2018. Besides, dysregulated autophagy is closely involved in the resistance of small-molecule drugs (e.g., vemurafenib) in thyroid cancers , Wei et al 2017. We herein review the potential role of autophagy in mediating the initiation, development and progression of thyroid cancers and highlight how autophagy interferes with the dedifferentiation process of thyroid cancers.…”
Section: Figurementioning
confidence: 99%
“…Similarly, BRAF or RAS mutant thyroid cancer cell lines tend to have a higher level of autophagy following drug treatment (Bikas et al 2015, Plews et al 2015. Wei et al recently found that following vemurafenib treatment, mitochondrial respiration and ATP production in thyroid cancer cells (K1 cells) increased significantly (Wei et al 2017), indicating increased mitochondrial metabolism as a potential mechanism for vemurafenib resistance. Obatoclax, an experimental Bcl2 inhibitor, could successfully overcome vemurafenib-induced resistance by reducing ATP production and suppressing the activity of autophagy in thyroid cancer cells (Wei et al 2017).…”
Section: Autophagy In Molecularly Targeted Therapy Of Thyroid Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to therapy is a major concern in cancer treatment. OBT has shown great response in resistant cancer cells and has overcome chemoresistance in different cancers [ 153 , 154 ].…”
Section: Ionophoresmentioning
confidence: 99%